Feedback Learning In Faculty of Hotel & Tourism, UiTM Terengganu: A millennial’s Perspectives - Abdullah, Rahman (Advances in Social Sciences Research Journal, 2019)
: Feedback learning in practical classes is seen as an important tool to gain input for improvisation, however, due to inconsistency of rubrics, assessment and the nature of formative feedback among lecturers, it is difficult to be conducted. Feedback learning with the help of technology (helps in standardizing assessment rubrics and timing of quality feedbacks, enable this information to be delivered to the students and lecturers gain knowledge in the process. The millennials seems to place high importance in feedback learning through technology since this functions as a medium for them to improvise in many aspects.